A Computed Microtomography Method for Understanding Epiphyseal Growth Plate Fusion - Staines, Katherine A.; Madi, Kamel; Javaheri, Behzad; Lee, Peter D.; Pitsillides, Andrew A. (Frontiers in Materials, 2018)
The epiphyseal growth plate is a developmental region responsible for linear bone growth, in which chondrocytes undertake a tightly regulated series of biological processes. Concomitant with the cessation of growth and sexual maturation, the human growth plate undergoes progressive narrowing, and ultimately disappears. Despite the crucial role of this growth plate fusion ‘bridging’ event, the precise mechanisms by which it is governed are complex and yet to be established. Progress is likely hindered by the current methods for growth plate visualisation; these are invasive and largely rely on histological procedures. Here we describe our non-invasive method utilising synchrotron x-ray computed microtomography for the examination of growth plate bridging, which ultimately leads to its closure coincident with termination of further longitudinal bone growth. We then apply this method to a dataset obtained from a benchtop microcomputed tomography scanner to highlight its potential for wide usage. Furthermore, we conduct finite element modelling at the micron-scale to reveal the effects of growth plate bridging on local tissue mechanics. Employment of these 3D analyses of growth plate bone bridging is likely to advance our understanding of the physiological mechanisms that control growth plate fusion.